Stereophotographs for scientific purposes - Remejin, Jacob M. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The application of stereo photography can provide more information than that obtained from simple photographs due to the three-dimensional view obtained during observation. A method is described for taking two photographs with a single simple camera. To determine the distance between the two stations of the camera, a formula and some modifications of it have been developed. The use of the formulas is shown with his problems in the field of forestry, but also with applications in several other fields of science.